Acute respiratory distress syndrome due to severe pulmonary tuberculosis treated with extracorporeal membrane oxygenation: A case report and review of the literature. (2016) - Omote, Norihito; Kondoh, Yasuhiro; Taniguchi, Hiroyuki; Kimura, Tomoki; Kataoka, Kensuke; Hasegawa, Ryuichi; Hasegawa, Yoshinori
Abstract: Mortality in patients with pulmonary tuberculosis remains high, especially in those who develop acute respiratory distress syndrome (ARDS). We report on a-48-year-old man with ARDS due to severe pulmonary tuberculosis who was rescued by extracorporeal membrane oxygenation (ECMO). He was initially hospitalized in the intensive care unit and noninvasive positive-pressure ventilation started. He was also administered anti-tuberculosis drugs and received systemic corticosteroid therapy. Six days later, further deterioration of gas exchange prompted the decision to intubate. However, he experienced progressive deterioration of arterial oxygenation despite conventional ventilatory support. We therefore decided to administer ECMO on day 9. After initiation of these treatments and ECMO support, pulmonary infiltrate and oxygenation status gradually improved and ECMO was discontinued on day 52. The patient was finally discharged from our hospital without severe disability. ECMO should be considered one of the treatment options for the management of ARDS due to severe pulmonary tuberculosis.